Ford County : stories - Grisham, John. (New York : Doubleday, 2009)
John Grisham returns to Ford County, Mississippi, the setting of his first novel, "A Time to Kill," with this collection of stories.
Blood drive -- Fetching Raymond -- Fish files -- Casino -- Michael's room -- Quiet haven -- Funny boy.
Keywords: Mississippi -- Fiction; Short stories